Religious Ignorance of Modern Indonesian Muslims in Multiculturalism - Siti Saridah (al-Afkar, Journal For Islamic Studies, 2024)
This paper concerns to analysis modern Indonesian Muslims in multiculturalism. It delineates the impact of multiculturalism lead toward Muslims’ religious ignorance. Then, the major theory is contemporary issues in Islamic studies. To seek toward the goals, the researcher uses qualitative study by doing observation and interview number of Muslims’ people randomly whether learners, educators, employees, entrepreneurs, civil societies and so on. They involve local and remote participants. Basically, there is not limitation of number of participants. There are significant matters that can be concluded. Firstly, to define the categorizes of religious ignorance has been practiced by modern Indonesian Muslims in multicultural country, when it happened and the reasons that modern Indonesian Muslims cannot be separated by doing religious ignorance. The result of this research is quite useful for Islamic educators and Islamic intellectuals in specifically and generally, for parents and relates parties who need to know the real condition of modern Indonesian Muslims to follow up the problems.